House Rating Schemes From Energy to Comfort Base - Kordjamshidi, Maria; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"House Rating Schemes" provides information to students, architects and researchers in the field of the built environment. It reviews current House Rating Schemes (HRS) used in different countries and investigates how these schemes assess the thermal performance of a house. It challenges the way that these schemes assess building energy efficiency and their inability to evaluate free running buildings which do not need an energy load for heating and cooling indoor environments. Finally, the book proposes a new index and method for HRS in which the efficiency of a house design can be evaluated with reference to its thermal performance in both free running and conditioned operation modes. The book deals with various approaches and methods for rating buildings on the basis of different indexes, with implications for both energy efficiency and thermal comfort. It also guides readers through a computer simulation program for developing a rating system that evaluates and ranks building energy efficiency.
Introduction -- House Rating Schemes -- Thermal Comfort -- Modelling efficient building design: Efficiency for low energy or no energy?- Assembling a House Energy Ratings (HER) and House Free running Ratings (HFR) Scheme -- Appendix.
Keywords: Engineering; Architecture; Electric engineering; Renewable energy sources; Sustainable development; Engineering; Energy Technology; Building Types and Functions; Sustainable Development; Construction Management; Renewable and Green Energy